(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): What factors stimulate organizations to innovate? Purpose: The purpose of the research is to find out which stimulating factors motivate organizations to innovate. Method: In order to obtain the data we used a qualitative method, a compilation method, by which we summarized results of the other authors on the same topic, a comparative method for comparing internal and external stimulating factors and a deductive method by which we conclude from individual cases in general Results: The research has shown that internal factors for innovation are different from external ones, and for the successful operation of the organization both of them are very important. Internal factors, among which include team work, praise, rewards, examples and actions of the leader, employee participation among themselves, organizational culture and the like, stimulate the thinking and development of improvement of the process, product and the way of work in the organization. External environmental factors stimulate innovation in order to increase the competitiveness of the company, and the organization faces changes in the market and product or service feedbacks. These are: suppliers, the sales market, customers, providers of new services, demographic change, etc. Organization: It is important for organizations to be aware of the importance of the factors that stimulate innovation and direct managers to stimulate motivation of their subordinates for new innovative proposals and reward them appropriately. Society: Theoretical starting points direct the company to greater attention in the awareness of the importance of innovation in its factors for the successful competitiveness of the organization on the market. Originality: The originality of the research is reflected in the breakdown of the stimulating factors of innovation to internal and external factors. Limitations/Future Research: For a broader view of the stimulating factors for the innovation of organizations, it would be necessary to examine more literature, incorporate inhibitory factors for innovation, and make a comparison between incentive and inhibitory factors.